Normal - Anderson, Jane.; Bull, Richard, 1924-; Mary Seibel; Danny Goldring; Jessica Lange; Tom Wilkinson; Hayden Panettiere; Randall Arney; Rich Komenich; Kirk Anderson; Christian Ambrose; Joe Foust; et al. (USA Avenue Pictures Productions, 2003)
After being married to Irma for 25 years, Roy decides the stress of being a woman in a man's body has grown intolerable. He unburdens himself to Irma and their pastor, shocking them both. Roy's decision to pursue a sex-change operation is greeted with intolerance and disgust by some of his co-workers and members of his church. Irma eventually comes to some understanding, and supports Roy through his journey to becoming "Ruth."
Languages: English, German Subtitles: English, German, Dutch, Bulgarian, Serbo-Croatian, Czech, Danish, Finnish, Norwegian, Polish, Portuguese, Romenian, Slovenian, Swedish, Turkish
Keywords: Drama